2019
DOI: 10.4142/jvs.2019.20.e74
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic profiles of biofilm, enterotoxins and virulence of Staphylococcus aureus isolates from dairy cows in Xinjiang Province, China

Abstract: As an important zoonotic pathogen, Staphylococcus aureus has led to serious mastitis and endometritis in infected dairy cows. In this study, a total of 164 strains of S. aureus were isolated from dairy cows in Xinjiang Province, China, and subjected to assays to determine drug susceptibility and biofilm (BF) formation ability. Enterotoxin-related genes were detected, and the transcription levels of genes related to BF formation were determined by using reverse transcription-quantitative polymerase chain reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…The presence of ST88 isolates carrying lukS/F-PV gene in veterinarians reminded us that humans could be reservoirs of PVL-positive S. aureus isolates and were at risk of infecting with PVL-positive S. aureus. Most of the previous studies focused primarily on SEs causing Staphylococcal food poisoning (SFP) [45][46][47][48][49][50]. Our results showed that SEs genes (sea, seb, sed-sej, seg-sei-sem-sen-seo, seh and sek) expressed specific host specificity.…”
Section: Discussionmentioning
confidence: 67%
“…The presence of ST88 isolates carrying lukS/F-PV gene in veterinarians reminded us that humans could be reservoirs of PVL-positive S. aureus isolates and were at risk of infecting with PVL-positive S. aureus. Most of the previous studies focused primarily on SEs causing Staphylococcal food poisoning (SFP) [45][46][47][48][49][50]. Our results showed that SEs genes (sea, seb, sed-sej, seg-sei-sem-sen-seo, seh and sek) expressed specific host specificity.…”
Section: Discussionmentioning
confidence: 67%
“…Concordant results were obtained by Rodríguez-López et al, who studied the presence of biofilm-forming MRSA in pigs and showed that, although most isolates were biofilm-producers, most of the producers displayed low levels of biofilm production [ 52 ]. Studies conducted with S. aureus isolated from dairy also showed that most isolates were weak-biofilm producers [ 56 , 57 , 58 ]. In our study, S. aureus isolates colonizing wild animals were strong biofilm producers.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotics are widely used in the clinical prevention and treatment of endometritis, which has increased the emergence of antibiotic-resistant bacteria, especially multidrug resistant (MDR) bacteria (Eslami et al 2015). It has been found that S. aureus is resistant to tetracycline (43.5%), penicillin (81%), erythromycin (44.5%), clindamycin (51.2%), and ciprofloxacin (30%) (Wu et al 2019). Meanwhile, the traditional screening of new antibacterial has suffered a considerable decline (da Cunha et al 2017).…”
Section: Introductionmentioning
confidence: 99%